Variation of linear and nonlinear parameters in the swim strokes according to the level of expertise. - Barbosa, Tiago (2017)
The aim was to compare the variation of the nonlinear behaviour in subjects with different levels of swimming expertise among the four swim strokes. Seventy-five swimmers were split into three groups (highly-experts, experts and non-experts) and performed trials at the four competitive swim strokes. The hip´s speed was collected over the trials being computed the speed fluctuation (dv), approximate entropy (ApEn) and fractal dimension (D). There was not an expertise x stroke interaction for the dv, albeit simple main effects of the expertise level and the swim stroke were verified. ApEn showed an expertise x swim stroke interaction. There was no expertise x stroke interaction for the D. Simple effects of the swim stroke and the expertise level were obtained. As a conclusion, swimming does exhibit nonlinear properties being its magnitude different according to the swim stroke and the level of expertise of the performer.